Analysis of subtelomeric virulence gene families in Plasmodium falciparum by comparative transcriptional profiling - Witmer, Kathrin (2013)
The Plasmodium falciparum genome is equipped with several subtelomeric gene families that are implicated in parasite virulence and immune evasion. Members of these families are uniformly positioned within heterochromatic domains and are thus subject to variegated expression. The best-studied example is that of the var family encoding the major parasite virulence factor P. falciparum erythrocyte membrane protein 1 (PfEMP1). PfEMP1 undergoes antigenic variation through switches in mutually exclusive var gene transcription. var promoters function as crucial regulatory elements in the underlying epigenetic control strategy. Here, we analysed promoters of upsA, upsB and upsC var, rifA1-type rif, stevor, phist and pfmc-2tm genes and investigated their role in endogenous gene transcription by comparative genome-wide expression profiling of transgenic parasite lines. We find that the three major var promoter types are functionally equal and play an essential role in singular gene choice. Unlike var promoters, promoters of non-var families are not silenced by default, and transcription of non-var families is not subject to the same mode of mutually exclusive transcription as has been observed for var genes. Our findings identified a differential logic in the regulation of var and other subtelomeric virulence gene families, which will have important implications for our understanding and future analyses of phenotypic variation in malaria parasites.